Fabrication of polydimethylsiloxane-derived superhydrophobic surface on aluminium via chemical vapour deposition technique for corrosion protection. (November 2017) - Sun, Wen; Wang, Lida; Yang, Zhengqing; Li, Sijia; Wu, Tingting; Liu, Guichang
Highlights: A facile and scalable method for preparing superhydrophobic Al was developed. The resultant superhydrophobic Al has a contact angle as high as 158.7°. The superhydrophobic Al showed a high and durable corrosion resistance to NaCl solution. The hydrophobic film itself served as a protective coating in Wenzel wetting state. Abstract: In this paper, a facile method based on the combination of chemical-etching and chemical vapour deposition is developed for the fabrication of superhydrophobic polydimethylsiloxane-derived film on aluminium substrate. It is revealed that the fabricated superhydrophobic aluminium has a static water contact angle as high as 158.7°, a good self-cleaning property and a persistent high corrosion resistance to 3.5 wt.% NaCl solutions. The presented method provides a scalable route to endow metals and alloys with multiple functions, making them suitable for the applications that need waterproof, dustproof and corrosion resistance properties.